2022
DOI: 10.1007/s10967-022-08195-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiological investigation of natural carbonated spring waters from Eastern Carpathians, Romania

Abstract: The current study presents a radiological water-quality assessment on 64 spring water samples from four Romanian counties. The study area is abundant in CO2-rich spring waters consumed by locals and tourists. Gross alpha activities ranged between 21 ± 2 and 7530 ± 658 mBq L−1, with 27% of the samples exceeding the WHO threshold. Gross beta values ranged from 40 ± 2 to 5520 ± 430 mBq L−1, with 29% exceeding the recommended values. Radionuclide activities fluctuated between 0.6 ± 0.08 and 81 ± 6 Bq L−1 for 222Rn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Regarding the radioactivity of groundwater, similar results were reported in the Galati region of Romania, the highest gross alpha and beta activities being found in samples collected from drilled wells [74]. Recently, a radiological investigation of 64 samples of natural carbonated water originating from four Romanian counties, namely, Covasna, Harghita, Bistrit , a-Năsăud, and Maramures , revealed that 53.5% and 26% of the investigated samples exceeded the allowed values for gross alpha activity and gross beta activity, respectively, which was attributed to the presence of volcanic rocks in the studied area [75].…”
Section: Radioactivity Parameters Of Drinking Water In the Studied Areamentioning
confidence: 89%
“…Regarding the radioactivity of groundwater, similar results were reported in the Galati region of Romania, the highest gross alpha and beta activities being found in samples collected from drilled wells [74]. Recently, a radiological investigation of 64 samples of natural carbonated water originating from four Romanian counties, namely, Covasna, Harghita, Bistrit , a-Năsăud, and Maramures , revealed that 53.5% and 26% of the investigated samples exceeded the allowed values for gross alpha activity and gross beta activity, respectively, which was attributed to the presence of volcanic rocks in the studied area [75].…”
Section: Radioactivity Parameters Of Drinking Water In the Studied Areamentioning
confidence: 89%